Evaluasi Efektivitas Diklat Pengemudi Angkutan Umum terhadap Kinerja Perilaku dan Kepuasan Penumpang dengan Pendekatan Terpadu Analitis - Budi Mardikawati; Aris Budi Sulistyo; Rahmat Ahmad; Yusime Fitasari; Handoko Handoko (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2025)
The improvement of public transportation service quality is highly influenced by the competence, performance, and behavior of drivers, who serve as the frontline of service delivery. The Public Transport Driver Certification Training (SPAU) is conducted to enhance professionalism, driving safety, and service ethics; however, its effectiveness in the field needs to be evaluated comprehensively. This study aims to assess the effectiveness of SPAU training on drivers’ performance and behavior, as well as its impact on passenger satisfaction, using an integrated analytical approach. The research employs a quantitative approach with data triangulation from drivers, their direct supervisors, and passengers. Analyses are conducted using Structural Equation Modeling (SEM) to examine causal relationships among variables, Importance Performance Analysis (IPA) to identify service attributes requiring priority improvement, and the Customer Satisfaction Index (CSI) to measure overall passenger satisfaction. The results indicate that competencies acquired from the training significantly influence improvements in drivers’ performance and behavior, which in turn positively affect passenger satisfaction. IPA analysis reveals several service attributes that still require improvement, while the CSI score shows that overall passenger satisfaction falls within a good category. These findings underscore the importance of strengthening the curriculum, providing post-certification guidance, and implementing continuous monitoring to ensure the sustainability of the training’s impact on public transportation service quality.